Faculty Members' Mindset Profiles in Research Career Development: Preliminary Evidence for Positive Psychology-Based Mentoring in a Muhammadiyah-Affiliated University - Ainur Rosidah; Sunyono Sunyono; Hasan Hariri; Muhammad Nurwahidin; Rabiyatul Adawiyah (Women, Education, and Social Welfare, 2026)
Research engagement is constrained not only by skills and resources but also by how faculty members interpret feedback, failure, and capability development. This preliminary cross-sectional survey mapped research-career mindset profiles among 32 faculty members representing five faculties at Universitas Muhammadiyah Pringsewu, a Muhammadiyah-affiliated university in Indonesia. A structured questionnaire addressed beliefs about research competence, publication challenges, academic failure, and career growth. Descriptive analysis and Wilson 95% confidence intervals were used. Three faculty members (9.4%; 95% CI: 3.2%-24.2%) were classified as fixed-mindset, seven (21.9%; 11.0%-38.8%) as growth-mindset, and 22 (68.8%; 51.4%-82.0%) as mixed-mindset. The predominance of mixed profiles indicates openness to developing research competence alongside continuing doubts about revision, rejection, and methodological demands. Rather than treating research engagement as merely a technical deficit, the findings identify a human-factors need for mentoring that combines research-skill support with strengths-based feedback, mastery experiences, and psychosocial support. The results are descriptive and cannot establish causality or psychometric validation. They provide a baseline for developing and testing a positive psychology-based research mentoring model.